The Role of Parents in Christian Religious Education in the Family towards Shaping the Character of Generation Z Children in Facing the industry 5.0 Era - Nursenta Dahliana Purba; Probo Retno (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
A strong generation in facing every development of the times is a generation that has strong and good character. Technological sophistication that presents new innovations through digital technology also makes the transition of human life enter the digitization era. Electronic devices have become the most preferred communication tool because they are equipped with various interesting features and can be used effectively, efficiently and interactively. The Z generation, known as the technology generation, has been familiar with the features in digital technology. This generation is vulnerable to negative impacts of digital technology development if its use is wrong. The method used in this study is a qualitative research method with a literature approach to answer the role of parents in Christian religious education in the family towards shaping the character of children. Religious education in the family is the foundation for shaping the character of every generation. Misuse of technology devices in this era has resulted in the decline of human morality. Therefore, it is very important to have guidance, mentoring, and supervision of children in instilling divine character values ​​to the next generation. The sophistication of technology in the Industry 5.0 era has awakened the hearts of parents to pay more attention to the education, guidance, and supervision of children in the family. Because God entrusted this task to parents. Parents who perform their role well will save generations who have a fear of God and have divine characters.